En ny avantgarde? - Nye stemmer, nye udgivelser, nye teknologier - Doubinsky, Sébastien (Passage - Tidsskrift for litteratur og kritik, 2012)
Sébastien Doubinsky: “A New Avant-Garde? New Voices, New Publishing Houses and New Technologies on the French Literary Scene” With the development of the Internet and the emergence of new approaches and technologies, we witness a growing amount of literature or literary forms based on the Internet on the French scene, as French writer and publisher François Bon observes in his essay, Après le livre. This short presentation focuses on three examples that serve as illustrations of the shift taking place (François Bon, Thibault de Vivies, a French writer whose work develops both on the page and the cyberpage, and the author himself, whose Éditions du Zaporogue use the print-on-demand possibility) in order to try and define the possibilities and limits of the Internet in the French literary landscape.